Still waters run deep: self-control as a moderator of dark personality traits for antisocial conduct and violent attitudes - DeLisi, Matt (The journal of forensic psychiatry & psychology, 2024)
Although self-control is frequently comorbid with other antisocial features, some individuals who exhibit psychological risk factors for antisocial conduct nevertheless have relatively high self-control. With this complexity in mind, the current study examined self-control as a potential moderator of antisociality/criminality features and violent attitudes using a community sample of 354 adult participants from Portugal. We found significant evidence that self-control moderates the dark core of personality when predicting antisociality/criminality, but not when predicting violent attitudes. We also found self-control moderates psychopathy when predicting antisocialty/criminality, but self-control had more robust moderation effects for violent attitudes. Specifically, self-control moderated narcissism, psychopathy, and sadism. Self-control did not moderate Machiavellianism in either model. Findings corroborate the notion that self-control plays an important role in moderating some dark traits of personality that are significant predictors for antisocial/criminal behaviors.